Juvenile Nasopharyngeal Angiofibroma - Excision Through Lateral Rhinotomy and Sublabial Approach - A Case Report - Sinha, NK; Rashid, MH; Shaheen, MM; Talukder, DC; Fakir, MAY; Hussain, MZ (Journal of Dhaka Medical College, 2011)
Juvenile angiofibroma is a rare hypervascular, locally aggressive benign tumour which is exclusively found in the nose and paranasal sinuses of male adolescents. The definitive treatment for this tumour is complete surgical excision. Different surgical approaches are used for complete excision. Most recent development is excision of the tumour using endoscopes. But in certain cases with large size and different extensions, open transfacial approaches are the choice for complete removal and for less operative bleeding, which are the main challenges for surgical excision of this tumour. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8587 J Dhaka Med Coll. 2011; 20(1) :78-81